Job Readiness Training to Improve Career Orientation for Generation Z - Ivonesti, Syarifah; Mahsuri (TAAWUN, 2025)
This community dedication aims to provide work readiness training to improve career orientation for Generation Z. The implementation of the service activity involved 60 students of SMKN 1 Bengalis who are in the Generation Z category. The training method used was discussion: groups, lectures, discussions, debriefs, experience learning, watching videos, films, games, and resource persons also convey their experiences and the experiences of other people who support them in getting a job. The time for implementing community service activities is divided into three periods: (1) the preparatory period; (2). Training implementation period (3). Evaluation. At the beginning of the training, participants are given a pre-test. At the end of the training, they are given a post-test and evaluation regarding the material, resource person or trainer, learning process, facilities and implementation. The material provided includes (1). Career orientation material, (2). Personal potential material, (3). Information material related to work or career (4). The material for determining goals or objectives is continued with material (5) Action plan material in designing the future regarding career, (6) Closing. Based on the results of measurements that have been carried out, it shows that work readiness training can improve the career orientation of participants, in this case Generation Z, so that they can direct Generation Z to increase opportunities for Generation Z to obtain decent work and pursue a career according to their potential in the future.